The Role of Islamic Religious Education Teachers in Shaping Islamic Character at MAS Al Washliyah Lubuk Pakam - Indah Nurjannah; Munawir Pasaribu; Rizka Harfiani (Indonesian Journal Education, 2025)
Character education is a crucial component of the national education system in addressing the challenges of globalization, moral decline among youth, and the weakening of spiritual values in daily life. Various social symptoms—such as reduced respect toward teachers and parents, dishonesty, and deviant behavior—indicate that character formation has not been carried out optimally in both family and school environments. This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students’ Islamic character at MAS Alwashliyah Lubuk Pakam. Using a qualitative descriptive approach, data were obtained through interviews, observations, and documentation involving PAI teachers, students, and the school principal. The findings reveal that PAI teachers function not only as educators but also as spiritual guides, motivators, and role models who internalize Islamic values through habituation of worship, integration of religious teachings in learning activities, and religious-based extracurricular programs. Character formation is strengthened by a supportive school culture and conducive policies, yet hindered by negative social media influence and insufficient parental guidance. Overall, the study confirms that synergistic collaboration between teachers, schools, and families is essential in fostering Islamic character that is both internalized and practiced consistently by students.